Importance of Agnikarma in Surgery – A Review Article - Trivedi, Sanjay L.; Toshikhane, Hemant; Sonani, Snehal R. (Journal of Neonatal Surgery, 2025)
Acharya Sushruta, revered as the father of surgery in Ayurveda, classified Agnikarma as one of the Anushastras, or Para surgical procedures. He posited that conditions unresponsive to Bheshaja (medicinal treatments), Shastra (surgical interventions), or Ksharkarma (alkaline cauterization) could be effectively managed through Agnikarma. Furthermore, diseases treated with Agnikarma are believed to have a low recurrence rate, underscoring its therapeutic efficacy. In contemporary times, there is a growing demand for rapid pain relief, and Agnikarma stands out as a swift and effective procedure for alleviating pain, also known as Vedana. Modern medicine recognizes Agnikarma as therapeutic burns or cauterization, a technique that has evolved from ancient practices. It serves multiple purposes: as a preventive measure, a postoperative procedure, and a haemostatic intervention. Agnikarma is particularly beneficial for disorders affecting the bones (Asthi), joints (Sandhi), ligaments, and tendons (Snayu). Ayurveda, as an enduring and comprehensive system of medicine, emphasizes not only the treatment of diseases but also the promotion of health. The ultimate goal of medical science is to enhance human well-being by eradicating diseases without causing adverse side effects. Ayurvedic treatments encompass Shamana (palliative) and Shodhana (purificatory) therapies. Among the various procedures outlined in Ayurvedic texts, such as Ksharkarma and Lepanam, Agnikarma holds significant importance. In today's fast-paced lifestyle, patients often seek immediate relief from pain, and Agnikarma offers a rapid solution. Many classical texts, including Charaka, Sushruta, Vagbhatta, and Harita, provide detailed descriptions of Agnikarma, covering its indications, contraindications, and techniques. Acharya Dalhana, in his commentary, elaborates on the different forms of Agnikarma, highlighting its versatility. This ancient practice forms the foundation of modern cauterization techniques. This review aims to provide comprehensive insights into Agnikarma, enhancing understanding and appreciation of this time-honoured therapeutic approach.